Pembiasaan Shalat Zuhur Berjama’ah Siswa di MtsS Al-Manaar Batuhampar Akabiluru Kabupaten Lima Puluh Kota - Huzni Fadilla; Januar Januar; Endri Yenti; Alimir Alimir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was based on a phenomenon that occurred when researchers saw that several pupils skipped the congregational lunchtime prayers. The execution of congregational prayers at this school is carried out in stages because the prayer room cannot accommodate all students. However, on the other hand, there is a gap in students' habituation in participating in congregational prayers at this school. This is proven by the fact that there are still some students who violate school rules (rules and regulations) such as not participating in congregational prayer activities, liking to come late, not being serious about carrying them out, some even deliberately skipping classes before time, and so on. The research type used in this essay is qualitative descriptive. The location of this study is MTsS Al-Manaar Batuhampar. The study included class VIII students as primary informants, with additional input from the school administration, student affairs representatives, and instructors. The author used documents, interviews, and observations to gather data. The author conducted an analysis of the data after its collection. Next, the author used data triangulation to confirm the accuracy of the data. According to the study's findings, it indicates that the congregational noon prayer is a program that has existed at MTsS Al-Manaar for a long time. The aim is to find out how midday prayers are carried out in congregation and also to know the supporting and inhibiting factors for carrying out congregational prayers. Supporting factors for carrying out congregational prayers are friendship, understanding of religion, motivation. The inhibiting factors are the environment, low student desire, and lack of facilities.